Can we enhance athletic performance using non-invasive brain stimulation? - Andre, J. (Murdoch University, 2017)
Recent research has shown athletic performance to be enhanced using non - invasive brain stimulation. One factor influencing an athlete`s performance is their perception of how hard an exercise task is, known as their rating of perceived exertion (RPE). Research has shown RPE to be modulated by fatigue. There is evidence to suggest that when fatigue occurs, there is reduced output from the primary motor cortex (M1) and the dorsolateral prefrontal cortex (DLPFC) to the muscles, which contributes to an increase in an athlete`s RPE. Therefore, using anodal transcranial direct current stimulation (A-tDCS) to increase cortical excitability could prolong the development of fatigue, and accordingly reduce RPE. If less effort is needed to perform the physical activity, then heart rate (HR) will decrease and performance will be enhanced. To test whether A-tDCS can enhance athletic performance and reduce RPE and HR, 10 athletic cyclists volunteered to complete four sessions. The first session was a Graded Exercise Test, and sessions two —four involved A-tDCS administered at one cortical site (M1, DLPFC, or Visual Cortex [control stimulation]) before participants completed a warm up, followed by a 16.1km Time Trial (TT). In each TT, HR, RPE, power output (PO), and time to complete the TT were recorded. Results showed no significant differences in RPE, HR, PO, or time to complete the TT between cortical sites. This study suggests that A-tDCS was unable modulate fatigue, and consequently, athletic performance, RPE, and HR remained unaffected. Reasons behind these findings are discussed, with suggestions for future research.